2000
DOI: 10.1159/000016377
|View full text |Cite
|
Sign up to set email alerts
|

How Renal Cells Handle Urea

Abstract: The urine concentration process requires an osmolality gradient along the renal cortico-medullary axis, with highest values in the renal papilla. NaCl and urea are the major solutes in the renal inner medulla, concentrations of urea up to 500-600 mM are found in the rat renal papilla. Urea can diffuse across cell membranes and contributes to balance intracellular and extracellular osmotic equilibrium. However, urea has perturbing effects on enzyme activity, and in concentrations above 300 mM is toxic for renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…In mammals and fish, changes in UT mRNA expression under a variety of osmotic environments have been reported. Smith et al (Smith et al, 1995) and Bagnasco (Bagnasco, 2000) demonstrated that dehydration increases the expression of UT-A2 mRNA in rat kidney. Morgan et al (Morgan et al, 2003) found that renal osmolytes and urea concentration were decreased and that renal UT transcripts (SkUT) were significantly diminished in response to environmental dilution in a marine elasmobranch.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals and fish, changes in UT mRNA expression under a variety of osmotic environments have been reported. Smith et al (Smith et al, 1995) and Bagnasco (Bagnasco, 2000) demonstrated that dehydration increases the expression of UT-A2 mRNA in rat kidney. Morgan et al (Morgan et al, 2003) found that renal osmolytes and urea concentration were decreased and that renal UT transcripts (SkUT) were significantly diminished in response to environmental dilution in a marine elasmobranch.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting system reabsorption of urea into the medullary interstitium is heavily involved in maintaining the interstitial osmotic gradient that underpins correct functioning of the countercurrent multiplier and urinary concentration [22]. Therefore, increased luminal and decreased interstitial concentrations of urea will contribute to increased urinary dilution independent of the loss of urea transporter expression.…”
Section: Discussionmentioning
confidence: 99%
“…13 Activation of KCC and stimulation of RVD occurs at concentrations of urea present in the renal medulla (100-600 mM). 45 Activation of KCC by urea is reversible, although volume reduction is not, so that progressive volume loss and CHC increase could occur during repetitive circulation through the kidney. The increase in sensitivity of SS RBCs to urea activation and the exaggerated volume reduction of SS reticulocytes in response to urea may contribute to the elevated CHCs observed in both SS reticulocytes and RBCs compared with AA cells.…”
Section: Discussionmentioning
confidence: 99%